SPORTS LOISIR AS A WAY OF IMPROVING THE QUALITY OF LIFE - IN THE VIEW OF SPECIALISTS IN THE FIELD OF PHYSICAL EDUCATION AND SPORT (University Arena, 2025)
Background. The idea of free time has been circulated since antiquity. Today, the concept of free time has a wide circulation. Increasing the quality of life is one of the basic concerns of modern society. Recreational leisure  activities contribute to well-being, have an essential role in maintaining the tone and maintaining health and implicitly improve the quality of life.Methods. Method of bibliographic study; The survey method, based on an interview, applied to a group of  experts in the field of physical education and sport.Results. Following the interview with experts in the field of physical education and sports, the following are examples: Experts appreciate the concept of quality of life as the result of education and gradually acquired by the individual. Systematic and continuous exercise of physical exercise induces a well-being with positive effects on quality of life.Conclusion. Following the qualitative research discussions with specialists in the field, the following conclusions can be drawn: Expert solutions also aim at increasing the number of hours allocated to institutionalized sports disciplines through curricula, but also increasing the quality of the educational act. Also, the modernization of existing sports facilities and the construction of new spaces for sport would stimulate the participation of young people in mass physical activities.
Keywords: sports loisir; quality of life; experts